EFEKTIVITAS METODE TUTOR SEBAYA BERBASIS YOUTUBE DALAM MENINGKATKAN KEMAMPUAN NUMBER SENSE MATEMATIS SISWA DITINJAU DARI PERBEDAAN JENIS KELAMIN PADA MATERI BILANGAN - Teti Trisnawati; Vina Vijaya Kusuma; Dwi Yulianto (LPPM Universitas Bina Bangsa, 2023)
This research is motivated by the majority of students in junior high school think Mathematics is a very difficult subject. The term number sense was introduced to refer to mathematical abilities where number sense has psychological and sociological factors where on average women show greater anxiety than men in mathematics. The purpose of this study was to see the effectiveness of the YouTube-based peer tutoring method in improving the number sense ability of students in class VII SMP Daar El Qolam 1,2,3 and 4 Kab. Tangerang. This type of research is experimental with a research population of 600 students. Sampling using cluster purposive sampling technique as many as 97 students consisting of 46 male students and 51 female students. Data collection is done by using NST measuring instrument. The data analysis technique used a paired sample t-test, (N-Gain), and a different t-test. The research findings show that there is a difference in the average value of number sense ability before and after the youtube-based peer tutoring method is carried out, for the results of the N-Gain analysis, it is found that the effectiveness of the youtube-based peer tutoring method in improving number sense skills is in the low category. There is no difference in the number sense ability of students in terms of gender differences in Daar El Qolam Middle School